Three new species of Gelechiinae (Lepidoptera: Gelechiidae) from India - Nandhini, D.; Shashank, P.r. (Zootaxa, 2025)
This study describes and illustrates three new species, Gelechia adi sp. nov., G. bilobuncusa sp. nov. and Istrianis ladakhensis sp. nov. (Lepidoptera: Gelechiidae: Gelechiinae) from India based on the characters of external morphology and the male and female genitalia. Diagnostic characters are provided and compared to similar species. All the specimens were collected during a recent faunistic survey in three Indian states, thereby expanding the knowledge of Indian Gelechiidae.